UNDERSTANDING TENOR IN SPOKEN TEXTS IN YEAR XII ENGLISH TEXTBOOK TO IMPROVE THE APPROPRIACY OF THE TEXTS - Meristiani, Noeris (Universitas Pendidikan Indonesia, 2011)
ABSTRACT: The goal of English Language Teaching is communicative competence. To reach this goal students should be supplied with good model texts. These texts should consider the appropriacy of language use. By analyzing the context of situation which is focused on tenor the meanings constructed to build the relationships among the interactants in spoken texts can be unfolded. This study aims at investigating the interpersonal relations (tenor) of the interactants in the conversation texts as well as the appropriacy of their realization in the given contexts. The study was conducted under discourse analysis by applying a descriptive qualitative method. There were eight conversation texts which function as examples in five chapters of a textbook. The data were analyzed by using lexicogrammatical analysis, described, and interpreted contextually. Then, the realization of the tenor of the texts was further analyzed in terms of appropriacy to suggest improvement. The results of the study show that the tenor indicates relationships between friend-friend, student-student, questioners-respondents, mother-son, and teacher-student; the power is equal and unequal; the social distances show frequent contact, relatively frequent contact, relatively low contact, high and low affective involvement, using informal, relatively informal, relatively formal, and formal language. There are also some indications of inappropriacy of tenor realization in all texts. It should be improved in the use of degree of formality, the realization of societal roles, status, and affective involvement. Keywords: context of situation, tenor, appropriacy.